Boosting productivity in Mexico through integration into global value chains - Dougherty, Sean (OECD Economics Department Working Papers, 2017)
Mexico's structural reforms are already boosting productivity, but more can be done. This paper focuses on issues that have led to the success of the "modern" Mexico, and have led to difficulties with the "traditional" Mexico. These include the success of Global Value Chains (GVCs) in advancing the trade integration and linkages of key sectors, as well as how competition problems, excessive local regulation, and weak legal institutions have led to misallocation across firms. This paper examines in particular Mexico's successful integration into GVCs. OECD research suggests that GVC participation can bring economic benefits in terms of productivity, diversification and sophistication of production. Understanding what drives integration into GVCs provides policy guidance to support a wider integration